Inovasi Sistem Penjadwalan Laboratorium Terpadu melalui Aplikasi M-Room berbasis Google Spreadsheet di Poltekkes Kemenkes Jakarta I - Hidayati, Auliya; Argianto, Argianto; Rini, Bekthi Pramudya (Jurnal Pengelolaan Laboratorium Pendidikan, 2025)
The digital transformation in educational laboratory management requires a scheduling solution that is efficient, transparent, and cost-effective. This study aims to design and develop M-Room, an integrated laboratory scheduling system based on Google Spreadsheet to support the moving room policy at Poltekkes Kemenkes Jakarta I. The platform leverages Google Spreadsheet's collaborative features to synchronize schedules in real time among users. System development followed the Waterfall model, which included requirements identification through stakeholder discussions, sheet structure design and data validation (using dropdown menus and automated formulas), the creation of an interactive dashboard for room availability visualization, implementation, and testing through simulation and user evaluation. The system was piloted over two semesters (January–December 2024) involving 70 participants, consisting of educational laboratory staff, lecturers, students, and administrators. Evaluation results indicated that 68.6% of users utilized the room booking feature, 42.9% checked room availability prior to scheduling, and 18.6% scheduled the use of integrated laboratories. All respondents (100%) rated the interface as user-friendly, while only 5.7% experienced minor issues. A total of 87.1% stated that the system significantly improved laboratory management, and 88.6% gave the highest score for overall user satisfaction. Active engagement with the system’s core features reflects strong user enthusiasm toward M-Room. These findings suggest that M-Room enhances scheduling efficiency, promotes cross-departmental collaboration, and offers a cost-effective, easy-to-implement, and scalable laboratory management solution. Future development is recommended to include integration with the academic information system (SIAKAD), the addition of automated notification modules, and the use of historical data analytics for optimizing laboratory capacity. Thus, M-Room is expected to serve as a foundation for adaptive and sustainable digital laboratory management. This innovation may serve as a model for collaborative Google Spreadsheet-based solutions in other vocational institutions.